Appellate Judicial Issues: Case Allocation and the Rule of Law - Butler, Petra (Victoria University of Wellington Law Review, 2002)
As part of the session on Appellate Judicial Issues, the author provides a brief introduction to the role of the judge in Germany. The author provides an introduction to the German Constitution (Grundgesetz-GG) and explores the importance of the words "lawful judge" in article 101 I 2 GG, as well as the implications surrounding jurisdiction and the constitutional principles underpinning them.